The Effect of Biofertilizer and Inorganic Fertilizer Toward The Nutrient Uptake in Maize Plant (Zea mays l.) - Yun Sondang; Khazy Anty; Ramond Siregar (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2019)
The productivity of land and plants have decreased slowly, due to the use of inorganic fertilizers continuously. Efforts to improve productivity are reducing inorganic fertilizers and returning organic matter to the soil. The aim of this research are (1) to identify the chemical characteristics of biofertilizer with an indigenous microorganism as bioactivators and (2) to study the effect of biofertilizer on nutrient uptake of maize plant. The research was conducted at Laboratory, Greenhouse, and Experimental Field of Politeknik Pertanian Negeri Payakumbuh, West Sumatra Indonesia. The first step experiment in the Laboratory was produced indigenous microorganism from banana humps. The second step of making bio-fertilizers in Greenhouse used a Completely Randomized Design with four treatments of indigenous microorganism (IMO) level 0%, 10%, 20%, 30% in biofertilizer with five replications. The third step of biofertilizer application on the Experimental Field used Randomized Block Design Factorial arranged with two factors and three replications, the first factor IMO level in biofertilizer (M) 0%, 10%, 20%, 30% and the second factor was the dosage of inorganic fertilizer (P) 0%, 50%, 100% of the recommended dosage, 12 combinations of treatments were obtained. Results showed that microbe consortium (Enterobacter cloacae, Bacillus subtilis, Pseudomonas fluorescens, Aspergillus niger, and Trichoderma asperellum) in biofertilizers with different levels would affect the chemical characteristics of biofertilizer. Biofertilizers influences nutrient uptake of P and K maize plant, while inorganic fertilizer influences nutrient uptake of N and P maize plant.